1988
DOI: 10.1111/j.1533-8525.1988.tb01252.x
|View full text |Cite
|
Sign up to set email alerts
|

The Free-Lance Musician as A Type of Non-Person: An Extension of the Concept of Non-Personhood

Abstract: Free-lance musicians are professionally trained artists who lack permanent membership in any musical organization. Although trained to be creative artists, most frequently free-lancers play supporting music for operas, ballets and solo performers on stage, or provide background music for dinners or receptions. As a consequence, their technical skills are devalued by audiences; they often play music below their skill level; spontaneity in interpretation is extremely limited or impossible; they are anonymous to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Even if this holds true also for the classical musicians, several of them complained about a derogatory attitude among orchestra musicians on permanent contracts towards them as freelancers, the idea being that they have not succeeded at auditions for orchestra positions. This “non‐person” categorization of the classical music freelance players by permanently employed orchestra musicians is in accordance with, for instance, Frederickson and Rooney (), who claim that freelancers “socialized to an ideal of personhood as artists, ... instead must consent to be principally non‐persons as support personnel. This conflict gives rise to problems of self‐appraisal and attendant coping strategies”.…”
Section: Interviewssupporting
confidence: 78%
“…Even if this holds true also for the classical musicians, several of them complained about a derogatory attitude among orchestra musicians on permanent contracts towards them as freelancers, the idea being that they have not succeeded at auditions for orchestra positions. This “non‐person” categorization of the classical music freelance players by permanently employed orchestra musicians is in accordance with, for instance, Frederickson and Rooney (), who claim that freelancers “socialized to an ideal of personhood as artists, ... instead must consent to be principally non‐persons as support personnel. This conflict gives rise to problems of self‐appraisal and attendant coping strategies”.…”
Section: Interviewssupporting
confidence: 78%
“…Avoidance-focused coping strategies reported in this study were previously identified as ignore/block things out (Jackson et al, 1998); avoidance and isolation ; detachment, denial, and wishful thinking (Madden et al, 1989); suppression of competing activities, wishful thinking, behavioral disengagement, denial, and self-blame (Crocker & Isaak, 1997); and creating a private world (Fredrickson & Rooney, 1988). Finally, failing in coping was an issue for 12 out of the 16 elite performers interviewed in this study and was previously reported in the literature as a problem in high-level performance (e.g., Crocker & Isaak, 1997;Wills & Cooper, 1988).…”
Section: Discussionmentioning
confidence: 88%
“…These mainly include qualitative studies, which focus on various different occupational aspects of educated and professional musicians from around the world (e.g. Cahn, 1992;Dyce and O'Connor, 1994;Frederickson and Rooney, 2016;Perrenoud and Bataille, 2017;Vaag et al, 2014;Publicover et al, 2019) and from Turkey (e.g. İmik and Haşhaş, 2016).…”
Section: Theoretical Background: Occupational and Cultural Implicatiomentioning
confidence: 99%